Hubungan Tingkat Pengetahuan Dan Sikap Ibu Terhadap Status Imunisasi Pada Balita Pasien Campak - Riza Savita; Elvira Elvira (Institut Citra Internasional, 2021)
Measles is the only cause of eczema with the characteristics of fever, cough runny, nose, conjunctivitis,erythematous maculopapula confluent rash,and pathognomonic enantema and explained that measles became one of the main causes of children death in 2007 – 2015. Research method description of correlation.The population of this study are mother / parents who have children aged 1 – 4 years and affected by measles and treated at Bakti Timah Pangkalpinang Hospital.The sampel of this study as much as 42 respondenrespondents based on data of patients affected by measles at Bakti Timah Hospital Pangkalpinang.Control sampling is taken by Non Sampling Probability.Data were analyzed by univariate and bivariate analysis using Chi – square test with significance level 0,05. The results showed that there is a relationship of variables with immunization status in toddler measles patients.The results showed that knowledge variables (POR = 7,741),Mother’s Attitude (POR = 6600). It is suggested that hospital can provide educational counseling to parents of children under aged five that the importance of measles immunization and the hazards of measles and to provide the participation of health workers in hospitals for good communication in patients and patients’ families with measles